SBA-15 and its carbon replica CMK-3 for rhodamine B adsorption - Moura, Luan do Nascimento de (2021)
Porous solid materials have been widely used in various fields to optimize physicochemical processes at an industrial level. Adsorption process has been widely studied due to its low application cost and high performance when applying porous materials. The application of molecular sieves in adsorption enables the study of the dynamics and optimization of such physical-chemical process. Mesoporous materials have great accessibility to bulky molecules such as organic compounds and dyes due to large pore opening. However, the chemical composition, specific area, and morphology of porous systems play a fundamental role in the adsorption of these compounds. Rhodamine B is an organic dye widely used in industry and was used in this study as a model molecule. Ordered mesoporous silica (SBA-15) and carbon-based (CMK-3) materials were used for the adsorption of Rhodamine B. The materials were synthesized and characterized by X-ray diffractometry (XRD), textural analysis by N2 adsorption, and infrared spectroscopy. The results show materials with a high specific area (> 600 m2 /g) and hexagonal arrangement of the pore system. Adsorption measurements show the high efficiency of CMK-3 in removing Rhodamine B (>99%), while SBA-15 only removes ~5%. The results indicate that the composition plays an important role in the adsorption process. Carbon materials are more interactive with the dye molecule than silica materials, confirmed by the thermogravimetry and pyrolysis analyzes. The by-products resulted by the CMK-3 samples thermal degradation after adsorption resulted in many complex compounds. The morphology and size of the channels have a strong relationship with the accessibility and adsorption of Rhodamine B. The arrangement of the straight pores of the SBA15 (6.5 nm average diameter) makes it difficult for the dye molecules dissolved in the solution to access, blocking the entry of pores by the first adsorbed molecules preventing the continuation of the adsorption process. Such behavior does not occur with CMK-3, since the mesopores of the material are open and guarantee good accessibility.